Customer Satisfaction Level in HDFC Bank (Among ATM & E-Banking Customers): A study on customer satisfaction and service quality in HDFC Bank (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In the days of intense competition, the banks are no different from any other consumer marketing company. It has become essential for the service firms in general and banks in particular to identify what the customer's requirements are and how those customer requirements can be met effectively. In the days where product and price differences are blurred, superior service by the service provider is the only differentiator left before the banks to attract, retain and partner with the customers. Superior service quality enables a firm to differentiate itself from its competition, gain a sustainable competitive advantage, and enhance efficiency. Primary as well as secondary data have been used for achieving the objectives of the study.